Economic Analysis of Sweet Potato Farming and Marketing in Odisha - Prakash, P; Kishore, Avinash; Roy, Devesh; Behura, Debdutt (JOURNAL OF ROOT CROPS, 2017)
Sweet potato plays a crucial role in increasing food security and income for the poor farmers of Odisha. Sweet potato is grown during Kharif and Rabi season. It is consumed in different forms namely fresh, boiled and baked. The value chain of sweet potato is not well organized in Odisha. This study was carried out to analyze the existing sweet potato value chain in four selected districts of Odisha namely Koraput, Kalahandi, Kandhamal and Ganjam. Purposive sampling technique was used to select the samples and primary data were collected through well-structured questionnaire from different value chain actors. Simple descriptive statistics and econometric analysis were used to analysis the data. The value chain actors in sweet potato are Input suppliers, producers, aggregators, wholesalers, retailer and consumers. There are no specialized traders or retailers of sweet potato found in the study area. They mostly sell the sweet potato along with vegetables. There were no processing unit for sweet potato in Odisha. Farmer’s producer organization (FPOs) and value addition will help in raising farmer’s income and welfare.